Mathematical models for studying the value of motivational leadership in teams - Solow, Daniel; Piderit, Sandy; Burnetas, Apostolos; Leenawong, Chartchai (My University, 2005)
Mathematical models are presented for studying the value of leadership in a team where the members interact with each other. The models are based on a leader's role of motivating each team member to perform closer to his/her maximum ability. These models include controllable parameters whose values reflect the amount of task interdependence among the workers as well as the motivational skill and variability in the skill of the leader. Confirming results - such as the fact that the skill level of the leader is a critical factor in the expected performance of the team - establish credibility in the models. Mathematical analysis and computer simulations are used to provide new managerial insights into the value of the leader - such as the fact that the skill of the leader can be more important than controlling the amount of interdependence among the team members and that having a choice of multiple leaders with no particular motivating skill is beneficial to the performance of small teams but not to large teams. © Springer Science + Business Media, Inc. 2005.
Keywords: Leadership; Motivation; NK model; Team replacement; Teams